Chiral all-organic nitroxide biradical liquid crystals showing remarkably large positive magneto-LC effects. Issue 20 (12th February 2016) - Suzuki, Katsuaki; Takemoto, Yusa; Takaoka, Shohei; Taguchi, Koji; Uchida, Yoshiaki; Mazhukin, Dmitrii G.; Grigor'ev, Igor A.; Tamura, Rui
Abstract : The liquid crystalline chiral nitroxide biradical ( S, S, S, S )-3 synthesized has shown much larger 'positive magneto-LC effects' in the chiral nematic (N*) phase than the monoradical ( S, S )-1 . Abstract : The liquid crystalline chiral nitroxide biradical ( S, S, S, S )-3 synthesized has shown much larger 'positive magneto-LC effects' in the chiral nematic (N*) phase than the monoradical ( S, S )-1 .